Agile processes in software egnineering and extreme programming – workshops : XP 2020 Workshops, Copenhagen, Denmark, June 8-12, 2020, revised selected papers /: XP 2020 Workshops, Copenhagen, Denmark, June 8-12, 2020, revised selected papers. (2020) - Unknown
No abstract available